Proniosomal Telmisartan Tablets: Formulation, in vitro Evaluation and in vivo Comparative Pharmacokinetic Study in Rabbits - Teaima MH; Yasser M; El-Nabarawi MA; Helal DA (Dove Medical Press, 2020)
Mahmoud Hasan Teaima,1 Mohamed Yasser,2,3 Mohamed Ahmed El-Nabarawi,1 Doaa Ahmed Helal4 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Horus University, New Damietta, Egypt; 3Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Sinai University, North Sinai, Egypt; 4Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Fayoum University, Fayoum, EgyptCorrespondence: Mahmoud Hasan TeaimaDepartment of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, EgyptTel +20 1005840264Email mahmoud.teaima@pharma.cu.edu.egObjective: The purpose of this study was to prepare proniosomal vesicles of Telmisartan (TEL) to be compressed into tablets which will be further evaluated in vitro and in vivo.Materials and Methods: An experimental design was adopted using surfactants of different HLB values (span 40-brij 35), different cholesterol ratios (20– 50%) and different phospholipid types (egg yolk-soyabean). Different responses were measured followed by tablet manufacturing. The highest EE was shown in F3 (85%) while the lowest value was obtained in F7 (8.4%). Finally, zeta potential results were in the range of − 0.67 to − 27.6 mv. Compressibility percent revealed that F5 showed an excellent flowability characteristic with a value of 9.74± 1.61 while F3 and F6 showed good flowability characteristics. By the end of the release, F6 showed approximately 90% drug release.Results: F6 was selected for the in vivo study; Cmax was increased by 1.5-fold while AUC0-∞ also increased significantly by 3-fold when compared with commercial tablet and finally, tmax was increased by 3-fold indicating sustained release pattern. The relative bioavailability was also increased by 3.2-fold.Conclusion: The results of this study suggested that the formulation of compressed tablets containing more stable proniosomal powder extended the release of TEL and increased its bioavailability as well.Keywords: telmisartan, TEL, proniosomal-derived niosomes, entrapment efficiency, EE, sustained-release tablet, bioavailability, multifactorial design